Internalizing Ecotheological Values: Strategies of Pesantren in Fostering Environmentally Conscious Character - Muhammad Diwanul Mujahidin; Ali Imron; Mochamad Hafid Abdiliah (Santri: Journal of Pesantren and Fiqh Sosial, 2025)
The ongoing environmental crisis in modern society requires urgent attention, as the universe was created with an inherent balance. This research investigates the ecotheological perspective developed within pesantren education, aiming to analyze the role of pesantren in fostering environmental awareness grounded in Islamic values. Pesantren possess significant potential to cultivate ecological awareness among santri by integrating Islamic teachings with local wisdom. This study employs a literature review method with a theoretical approach, analyzing sociological theories of religion relevant to pesantren education that support the internalization of ecotheological values. The findings demonstrate that pesantren can instill environmental values through an ecotheological approach. Specifically, pesantren can implement the principle of khalifah fi al-ardl, which emphasizes human responsibility as stewards of the universe (rahmatal lil alamin). Additionally, pesantren serves as platforms for Islamic scholars to develop environmental jurisprudence (fiqh al-bi'ah), which governs environmental protection. Furthermore, pesantren utilizes best practices to instill ecotheological values through contextual and experiential learning. Consequently, pesantren education can help cultivate a generation characterized by strong ecological awareness and a commitment to environmental sustainability.